The Problem of Violence Against Women in Terms of Media Reflections and Public Relations - PELTEKOĞLU, ZEYNEP FİLİZ (MARMARA UNIV, FAC COMMUNICATION, 2017)
Violence and violence against women can often arise in different forms, in terms of their structural characteristics, such as physical violence, psychological violence, sexual violence, deprivation and neglect and it might have biological, sociological and economic reasons. In order to prevent violence, the circumstances that lead to violence must be removed. We can mention legal, social, cultural and economic reasons which make it difficult to prevent violence. There is a need for a common literature and approach to prevent violence, as well as a common sense which handles all components together. In order to prevent violence against women and to fight against violence, it is necessary to determine the main problems and to take measures within the framework of institutional, social and individual dimensions by switching to broad-based common sense. The measures to be taken include the establishment of legal and economic regulations and the establishment of qualified public health policies. In order to explain all such arrangements, to overcome economic, cultural and / or social obstacles and to create an individual and social consciousness about legal regulations, a public relations strategy is needed which does not overshadow the current situation, reveals the problem and brings a solution to it. This study aims to emphasize the role of public relations in preventing violence and promoting gender equality. Within the scope of the research, which is conducted in order to understand the violence on women in terms of media reflections, Hurriyet Newspaper was selected as the most circulated newspaper in Turkey and by considering the diversity of reader profile that the newspaper has in 2017. Accordingly, an online archive scanning was performed between 1 January 2017 and 30 June 2017, by using the keywords woman and violence. The research that carried out in cooperation with the Ministry of Family and Social Policy and Hacettepe University and the data obtained from the newspaper scanning are largely compatible with the types and nature of violence results. Prevention and improvement of protective measures of violence against women seen as an important problem for Turkey, that should be addressed with an integrated approach. The study emphasized that combating violence is an important role of public relations. In this context in the light of research results of Hacettepe University, we can advise on combating violence against women, it is expected to be effective if planned and managed as a part of institutional, individual, and social categories.
Keywords: Public Relations; Woman; Media; Violence